Community Structure of the Parasites of the Endemic Chocolate Chub Squalius carinus Ozulug & Freyhof, 2011 (Cyprinidae) from Isikli Lake, Civril, Turkey - (:unkn) unknown (INST ZOOLOGY, BAS, 2017)
This study presents the first data on parasites of the chocolate chub, Squalius carinus Ozulug & Freyhof, 2011. The composition and the structure of the parasite community infecting this endemic fish from the Isikli Lake are described. A total of 54 specimens of S. carinus are examined; 51 (94.4%) infected by at least one parasite species. In total, 1192 parasite individuals are collected, with mean intensity of 23.4 and mean abundance of 22.1 parasites/fish. The parasite community of S. carinus consists of 14 species: Trichodina sp., Ichthyophthirius multifiliis, Chilodonella cyprini (Protozoa); cysts of Myxobolus sp. (Myxozoa); Dactylogyrus vistulae, Gyrodactylus sp. (Monogenea); Bothriocephalus acheilognathi (Cestoda), metacercariae of Diplostomum sp. and Thylodelphys clavata (Digenea); larvae of Nematoda indet. (Nematoda), Pomphorhynchus sp. (Acanthocephala); Lamproglena pzdchella and Lernaea cyprinacea (Crustacea); and glochidia of Mollusca indet. (Mollusca). The highest dominance index among parasites is recorded for Pomphorhynchus sp. (47.9%), and the lowest for Nematoda indet. (0.3%). The mean species richness of parasite infracommunities is 2.3 species per individual fish. The parasite community of S. carinus is dominated by Pomphorhynchus sp. The remaining parasite species are found with low prevalence and abundance, except for Diplostomum sp. and Dactylogyrus vistulae, which are moderately abundant.
Keywords: Fish; endemic Squalius carinus; parasite communities; Isikli Lake; NATIVE FISH; CARASSIUS-GIBELIO; ECOLOGY; CEPHALUS; CARP